2013
DOI: 10.1002/cssc.201300560
|View full text |Cite
|
Sign up to set email alerts
|

A Dication Cross‐Linked Composite Anion‐Exchange Membrane for All‐Vanadium Flow Battery Applications

Abstract: Multidisciplinary research on novel organic luminescent dyes is propelled by potential applications in plastic electronics and biomedical sciences. The construction of sophisticated fluorescent dyes around a tetrahedral boron(III) center is a particular approach that has fueled the creativity of chemists. Success in this enterprise has been readily achieved with simple synthetic protocols, the products of which display unusual spectroscopic behavior. This account is a critical review of recent advances in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 184 publications
1
27
0
Order By: Relevance
“…From 40 mA cm À2 to 100 mA cm À2 , the EE values (87.5%, 85.7%, 83.5%, 80.2%, at 40, 60, 80, 100 mA cm À2 , respectively) of cell with PyPPSU-2 membrane was higher than that (85.7%, 83.5%, 80.0%, 77.2% at 40, 60, 80, 100 mA cm À2 , respectively) of cell with Nafion 117 membrane. Furthermore, at a current density of 80 mA cm À2 the cell with PyPPSU-2 membrane showed an EE of 83.5%, which was comparable with the EE (84%) reported by Zhang et al [26] and EE (83.6%) by Zhang et al [28] under the similar test condition (80 mA cm À2 , 1.5 M V 2þ /V 3þ and 1.5 M VO 2þ /VO 2 þ in 3.0 M H 2 SO 4 ). Additionally, the cell with PyPPSU-2 showed high EE of 80.2% even at high current density of 100 mA cm À2 , which was higher than that of cell with Nafion 117 membrane (77.2%) under the same test condition.…”
Section: Membranesupporting
confidence: 90%
See 1 more Smart Citation
“…From 40 mA cm À2 to 100 mA cm À2 , the EE values (87.5%, 85.7%, 83.5%, 80.2%, at 40, 60, 80, 100 mA cm À2 , respectively) of cell with PyPPSU-2 membrane was higher than that (85.7%, 83.5%, 80.0%, 77.2% at 40, 60, 80, 100 mA cm À2 , respectively) of cell with Nafion 117 membrane. Furthermore, at a current density of 80 mA cm À2 the cell with PyPPSU-2 membrane showed an EE of 83.5%, which was comparable with the EE (84%) reported by Zhang et al [26] and EE (83.6%) by Zhang et al [28] under the similar test condition (80 mA cm À2 , 1.5 M V 2þ /V 3þ and 1.5 M VO 2þ /VO 2 þ in 3.0 M H 2 SO 4 ). Additionally, the cell with PyPPSU-2 showed high EE of 80.2% even at high current density of 100 mA cm À2 , which was higher than that of cell with Nafion 117 membrane (77.2%) under the same test condition.…”
Section: Membranesupporting
confidence: 90%
“…The results indicated that pyridinium groups were successfully introduced into the PyPPSU membrane. Additionally, the PyPPSU membrane displayed absorbance at around 3391 cm -1 , which was attributed to water bound to the ionic groups [26].…”
Section: Membrane Synthesis and Propertiesmentioning
confidence: 99%
“…The chloromethylated polysulfone (CMSPF) polymer was prepared through a common chloromethylation method. 25 …”
Section: Methodsmentioning
confidence: 97%
“…As one of the key components of VRBs, the ion exchange membrane (IEM) in the cell transports H + or SO 4 2À /HSO 4 À ions to complete the circuit while separating the anode and cathode electrolytes. In contrast, anion exchange membranes (AEMs) [16][17][18][19][20][21][22][23] reduce the permeation of vanadium ions due to the Donnan exclusion effect but are restricted by lower conductivity. At present, the most widely used IEMs are Naon series membranes (DuPont).…”
Section: Introductionmentioning
confidence: 99%